A Low-Complexity Analog Linear Coding Scheme for Transmitting Asymptotically WSS AR Sources - Gutierrez-Gutierrez, Jesus; Villar-Rosety, Fernando M.; Zarraga-Rodriguez, Marta; Insausti, Xabier (IEEE communications letters, 2019)
In this letter, we give a low-complexity analog linear coding scheme for transmitting finite-length data blocks of asymptotically wide sense stationary (AWSS) autoregressive (AR) sources through additive white Gaussian noise (AWGN) channels.